Aktivitas Antioksidan Ekstrak Daun Sirih Merah (Piper crocatum) Hasil Optimasi Pelarut Etanol-Air - AGATHA BUDI SUSIANA LESTARI; YOHANES DWIATMAKA (Fakultas Farmasi Universitas Pancasila, 2014)
Red bettle (Piper crocatum) is one of the plants which is extensively explored and has many biological activity. In this research, it is done the optimization of 96% ethanol and water composition as solvents in the process of extraction of red bettle leaves in percentage ratio of 100:0 (P1), 75:25 (P2), 50:50 (P3), 25:75 (P4), and 0:100 (P5) using Simplex Lattice Design (SLD). The aim of this research were to find the optimum composition of solvent which can obtain extract with the highest antioxidant activity. The antioxidant activity of red bettle leaves extract was measured by radical scavenging method using DPPH (diphenylpicryl hydrazyl), and assessed using parameter of EC50. The result showed that red bettle leaves extract which produced with ethanol-water as a solvent in percentage (%) of 75:25 (P2) has the higest antioxidant activity, with the smallest EC50’s value of 301,10 μg/ml.